Agroecology on a human scale in the department of Chilecito, La Rioja. Analysis in relation to the ODS (Papeles, 2023)
The objective of this talk is to analyze the weaknesses and strengths of the transition process towards a human scale agroecology of small horticultural producers in the Departmento de Chilecito (La Rioja), considering the Sustainable Development Goals (SDGs), established in the 2030 AGENDA. In Chilecito, under the context of the Covid-19 health emergency, an agroecological transition with these producers was promoted from the Institute of Family, Peasant, and Indigenous Agriculture, with the accompaniment of the Universidad Nacional de Chilecito. The main goal of the actions is a sustainable human scale agriculture that guarantees food security and sovereignty, which revealed vital for the community after the global economic imbalances caused by the Covid-19 pandemic and now, the Ukraine-Russia military conflict. In Argentina, the Bill for the Agroecology Promotion, and the country's commitments to the SDGs, provide and institutional support for the agroecological transition process. However, small horticultural producers face serious problems related to land and water access and the lack of training that allows them a true and sustainable transition towards an agroecological production.
Keywords: agroecology; sustainable development goals; 2030 agenda; environmental law; family farming